THE EFFECT OF USING COLLABORATIVE STRATEGY READING ON STUDENTS READING COMPREHENSION IN NARRATIVE TEXT AT TENTH GRADE OF SMAN 1 TEMBILAHAN - Ami Selvia; Maizarah Maizarah; Felci Tria Sauhana (J-Shelves of Indragiri (JSI), 2023)
This research aimed to know the effect of using Collaborative Strategy Reading on students reading comprehension at SMAN 1 Tembilahan. The researcher found several problem experianced by students in english, such as: Students had difficulty understanding reading texts, some students not able to get information from the text, students need much time to comprehend the text, and students have problems answering the reading passage. Collaborative Strategy Reading is useful for students skill in reading comprehension. The design of this research was the tenth grade of SMAN 1Tembilaha 2022/2023 academic year. The population of this research was 312 students consist of 9 classes. While, the sample of this research was two classes consist of 68 students. The sample of this class was X.MIPA5 as control group and X.MIPA4 as experimental class. To get the data of this research, the researcher gave test as insruments which included pre-test and post-test. For the pre-test and post-test in the form of multiple choices test, consist of 2o items questions for each. The learning prosess was three meetings. The finding of this research showed that the avarage score in pre-test was 38,5 while in post-test was 66,3 for the experimental group. The mean score of post-test was higher than the mean score of pre-test. The result of analysis, it showed that the value Tobserved 3,39 was higher than Ttable was 2,00 in significant 5% based on the result, it was provided that the null hypothesis (H0) was rejected and alternative hypothesis (Ha) was accepted. Therefore, there was a significant effect of Collaborative Strategy Reading on students reading comprehension at SMAN 1 Tembilahan